Rethinking the Paradigmatic Frameworks of Performance Measurement Systems in The Light of Recurring Globalized Crises - Sonia Snadli; Wafa Khlif; Lotfi Karoui (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research question- Is the failure of performance measurement systems (PMS) due to the crisis in itself or to a radical change in the paradigm that governs the world that has caused a loss of momentum? Motivation- In the era of recurrent/multiple crises, some researchers have signaled the inadequacy of the industrial economics paradigm and the managerial tools arising from them, and their inability to address the new characteristics of the environmental context. On this subject, we wonder whether the observed "malaise" of PMS is due to a possible paradigmatic obsolescence. If necessary, a redefinition of these systems should be considered so that the indicators regain their relevance. Idea- In recent decades, crisis meant no more than a temporary disruption of an idealized situation. The recurrence of systemic natural, social, economic and other crises and the ensuing volatile, uncertain, complex and ambiguous business environment has become the rule and we need to reappraise the capacity for our tools to grasp the complex reality of our world. Data/Tools- Building on complexity theory authors, the article aims to critically reflect on the paradigmatic foundations that give meaning (or not) to PMS. Findings- The recurrence of crises reflects an obsolescence of the dominant economic and managerial paradigm advocating determinism, simplicity and certainty/predictability. PMS must be redefined in order to regain their relevance in line with the paradigm characterized by volatility, complexity, uncertainty and ambiguity. Contribution- This paper makes two major contributions. First, we deconstruct the dominant model of performance assessment and measurement based on mechanistic industrial economics highlighting the limitations of traditional accounting methods in capturing the complex and dynamic nature of modern business environments. Second, we describe the main characteristics of the new business landscape and the original understanding of crisis to highlight the need to review traditional approaches to accounting indicators and performance measurement in this context of a complex, uncertain world.
Keywords: M40; 650; Performance Management Systems; Crises; Complexity; Managerial doxa